A new gigantic species from Turkey, Angelica turcica (Umbelliferae) - Hamzaoğlu, Ergin; Koç, Murat (Phytotaxa, 2016)
A new species, Angelica turcica, is described and illustrated. It is a highly distinct species that is immediately characterized by a gigantic habit, with large leaves and inflated sheaths. In fruit shape it resembles Angelica purpurascens, which is known in Caucasia, Turkey and Iran.